2010
DOI: 10.1038/aja.2010.71
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of spermatogenesis: from protein lists to understanding the regulation of male fertility and infertility

Abstract: Proteomic technologies have undergone significant development in recent years, which has led to extensive advances in protein research. Currently, proteomic approaches have been applied to many scientific areas, including basic research, various disease and malignant tumour diagnostics, biomarker discovery and other therapeutic applications. In addition, proteomics-driven research articles examining reproductive biology and medicine are becoming increasingly common. The key challenge for this field is to move … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…We reported protein expression of germ cells at different developmental stages, including meiotic and haploid germ cells, thereby identifying the proteomic profiles of cells associated with spermatogenesis (Guo et al 2010b(Guo et al , 2011. These data have helped to develop our understanding of the regulation of male fertility (Huang & Sha 2011). Several proteins reported in these studies were selected for further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…We reported protein expression of germ cells at different developmental stages, including meiotic and haploid germ cells, thereby identifying the proteomic profiles of cells associated with spermatogenesis (Guo et al 2010b(Guo et al , 2011. These data have helped to develop our understanding of the regulation of male fertility (Huang & Sha 2011). Several proteins reported in these studies were selected for further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Spermatogenesis is the process of the development of sperm from undifferentiated germ cells, via a precisely-regulated well-coordinated mechanism[16],[24]. In our previous research, we combined two-dimensional electrophoresis mass spectrometry (2DE-MS) and liquid chromatography (LC-MS) to construct a series of proteomic profiles of spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous research, we combined two-dimensional electrophoresis mass spectrometry (2DE-MS) and liquid chromatography (LC-MS) to construct a series of proteomic profiles of spermatogenesis. We also obtained a complete protein profile and proteinprotein interaction map during testicular development and spermatogenesis[16]. We selected a number of these proteins for further analysis, and in this study we investigated the localization and role of flotillin-2 during spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of the advances achieved so far include, descriptive proteomics such as the identification of sperm proteins (Baker et al., ), the proteins of human seminal plasma (Pilch and Mann, 2006) and bull epididymal secretions (Belleannee et al., ). Other studies described the evolutionary and functional analysis of reproductive proteins (Findlay and Swanson, ), spermatogenesis (Huang and Sha, 2011), the explanation of changes related to chromatin condensation (Oliva and Castillo, 2011), the description of proteome during testis development (Paz et al., 2006), sperm capacitation (Baker et al., ) and the analysis of sperm regions that mediate sperm–egg interactions (Stein et al., 2006). Proteomic research has been found to be important in the diagnosis of diseases in the reproductive system, such as prostatic cancer (Masters, 2011) or asthenozoospermia (Wang et al., 2009).…”
Section: Proteomicsmentioning
confidence: 99%